Chromosomal instability in human trophoblast stem cells and placentas - Danyang Wang; Andrew Cearlock; Katherine Lane; Chongchong Xu; Ian Jan; Stephen McCartney; Ian Glass; Rajiv McCoy; Min Yang (Nature Communications)
Abstract The human placenta, a unique tumor-like organ, is thought to exhibit rare aneuploidy associated with adverse pregnancy outcomes. Discrepancies in reported aneuploidy prevalence in placentas stem from limitations in modeling and detection methods. Here, we use isogenic trophoblast stem cells (TSCs) derived from both naïve and primed human pluripotent stem cells (hPSCs) to reveal the spontaneous occurrence of aneuploidy, suggesting chromosomal instability (CIN) as an inherent feature of the trophoblast lineage. We identify potential pathways contributing to the occurrence and tolerance of CIN, such as autophagy, which may support the survival of aneuploid cells. Despite extensive chromosomal abnormalities, TSCs maintain their proliferative and differentiation capacities. These findings are further validated in placentas, where we observe a high prevalence of heterogeneous aneuploidy across trophoblasts, particularly in invasive extravillous trophoblasts. Our study challenges the traditional view of aneuploidy in the placenta and provides insights into the implications of CIN in placental function.